Rodzina – jej wartość i znaczenie z perspektywy życia Dorosłych Dzieci Rozwiedzionych Rodziców - Piotrowska, Maja (Karkonoska Państwowa Szkoła Wyższa, 2012)
We live in a world where our values and beliefs passed from one generation to another are being redefined. The notions of marriage and family also receive different meanings. Persons involved in my research often stressed the great value they associate with this smallest social group. I think that their opinions and beliefs are the consequence of the fact that my interlocutors – as they admitted – did not experience things they were talking about themselves. On the other hand, their opinions about marriage and family are full of uncertainty and fear of impermanence. Such anxieties related to these crucial forms of relationships are typical of adult people. They do not seem to believe that their relationships can last forever. It is especially marriage that they see as impermanent, weak, and unstable,and as something likely to decay. They believe that the memories concerning their parents' divorce are proofs of their theories.
Keywords: rodzina; Dorosłe Dzieci Rozwiedzionych Rodziców; rozwód